Limit on the tau neutrino mass from τ→π-π+π-π 0ντ - Athanas, M; Avery, P; Jones, C; Lohner, M; Prescott, C; Rubiera, A; Yelton, J; Zheng, J; Brandenburg, G; Briere, R; Ershov, A; Gao, Y; et al. (2000)
From a data sample of 29058 τ+→π±π+π -π0ντdecays observed in the CLEO detector we derive a 95% confidence upper limit on the tau neutrino mass of 28 MeV. ©2000 The American Physical Society.